2021
DOI: 10.1212/cpj.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Seizure Associated With Kratom Use in Patients With Epilepsy

Abstract: Purposeof review: Kratom (mitragynine) is a commercially available herbal supplement that is gaining popularity in the United States (U.S.). Kratom is associated with a variety of neurological effects. This review will discuss kratoms association with seizure through three cases and highlight what neurologists should know about kratom's clinical effects and legal status.Recent findings:Kratom is currently commercially available, unscheduled by the U.S. Drug Enforcement Administration (DEA), and a topic of regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The current study identified significant signals of seizure (log OE ratio 3.15, 95% credibility interval: 2.50–3.60) and generalized tonic–clonic seizure (log OE ratio 2.6, 95% credibility interval: 1.05–3.59). There have been several reports of kratom‐associated seizures 36,37 . A 2018 case report suggested that kratom abuse might be able to induce structural brain lesions and recurrent seizures 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study identified significant signals of seizure (log OE ratio 3.15, 95% credibility interval: 2.50–3.60) and generalized tonic–clonic seizure (log OE ratio 2.6, 95% credibility interval: 1.05–3.59). There have been several reports of kratom‐associated seizures 36,37 . A 2018 case report suggested that kratom abuse might be able to induce structural brain lesions and recurrent seizures 38 .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of kratom‐associated seizures. 36 , 37 A 2018 case report suggested that kratom abuse might be able to induce structural brain lesions and recurrent seizures. 38 The mechanism of how these seizures occurred is not well‐understood, but adrenergic and stimulant effects are possible explanations.…”
Section: Discussionmentioning
confidence: 99%
“…51 Reports of harm in case reports and NPDS calls have included neurologic injury (seizures, encephalopathy, transient paralysis, and cognitive impairment), cardiopulmonary arrest, liver injury, hypothyroidism, hypogonadism, neonatal abstinence syndrome, and death (Table 2). 50,52,[57][58][59][60]68,79 Risk of adverse effects tends to increase with increasing dose, duration of use, additives, and concentration of formulation used. 18,52,53 Mortality risk associated with kratom is difficult to determine and is believed to be largely underestimated due to the complexity in testing for kratom.…”
Section: Potentiation Of Neuromuscular Blockadementioning
confidence: 99%
“…15,67 Furthermore, reports of death after kratom ingestion are strongly correlated with concurrent ingestion of other sedating substances, including prescription opioids, heroin, fentanyl analogs, benzodiazepines, and cocaine. 52,53 Some of these concurrent ingestions may have been intentional by users, considering that more than half of regular users surveyed between 2018 and 2019 reported polysubstance use Naltrexone 11,54 Drowsiness 14,50,51,55,56 Overdose reversal (if indicated) Confusion 14,51,57 Naloxone 26,56 Hallucinations 51 Supportive care for overdose symptom management Transient paralysis 57 Intravenous fluids 55,56 Seizures 14,51,55, 58 Anticonvulsants 55,58 Coma 51 Benzodiazepines 55 Cardiopulmonary N-acetylcysteine 49 Tachycardia 36,50,51 Ursodiol 49 Hypertension 36,50 Life-threatening organ failure management Prolonged QT c 55, 59 Advanced cardiac life support Respiratory depression 51,56 Liver transplantation 49 Cardiopulmonary arrest 51,53 Gastrointestinal Nausea 35,36,50 Vomiting 35,36,51 Liver injury or failure 49,60,61 Withdrawal symptoms Withdrawal treatment options Neurologic Kratom abstinence Irritability 7,14,[62][63][64] Naltrexone 11,54 Insomnia…”
Section: Potentiation Of Neuromuscular Blockadementioning
confidence: 99%
“…14 Literatures on various adverse effects from kratom including liver toxicity, seizure, abstinence syndrome, and even fatal complications have been emerging in the past 5 years after the possession and sale of kratom have been decriminalized in many countries. [15][16][17][18] Herein, we illustrate a patient with long COVID who developed acute mixed cholestatic-hepatocellular liver injury secondary to kratom used as a homemade iced cocktail called "4 × 100." An informed written consent was obtained from the patient for publication of this case report which has been approved by the ethics committee of Theptarin Hospital, Bangkok, Thailand (IRB No.…”
Section: Introductionmentioning
confidence: 99%